Towards Understanding Islam - Maudoodi, Syed Abul ʻAla, 1903-1979 (Lahore, Pakistan Iadra Tarjuman Ltd., 1998)
A simple, comprehensive introduction to Islam by a noted Muslim of the 20th Century, Sayyid Abul A'la Mawdudi.
Include Index
Keywords: Islam -- Islam--Doctrines